Surgical complications after Tenckoff catheter implant - Paweł Polski; Monika Kusz; Adam Alzubedi; Grzegorz Rudzki (Kazimierz Wielki University, 2020)
Peritoneal dialysis is one of the three basic methods of renal replacement therapy. It allows the patient to perform dialysis at home while maintaining the basic principles of asepsis. It involves the permanent introduction of a dialysis catheter into the peritoneal cavity. Surgical procedure is not complicated, however, as any intervention may carry the risk of complications. Depending on the time of diagnosis, complications are divided into early, up to 30 days after surgery and late - over 30 days after surgery. This paper aims to present the most common surgical complications associated with Tenckoff catheter implantation.